Assessing multi-channel consumers' convenience expectations of online order/in-store pickup service. (1st January 2014) - Ma, Hao; Su, Yong; Oh, Lih-Bin
'Online order/in-store pickup (OOIP)' service allows customers to self-collect their online orders from the retailers' physical store at their convenience. This service brings unprecedented control to multi-channel consumers in the order fulfilment process. This paper examines how the need for control, a fundamental psychological trait, impacts multi-channel consumers' expectation of the level of service convenience that OOIP provides. Data were collected from 351 Chinese consumers to assess the effect of a need for control on decision convenience, access convenience, transaction convenience and post-benefit convenience. Findings suggest that consumers' need for control positively affected their expectations on all four types of service convenience. We provide theoretical and managerial implications arising from the findings.